Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1128/jb.00394-18
|View full text |Cite
|
Sign up to set email alerts
|

Surfing Motility: a Conserved yet Diverse Adaptation among Motile Bacteria

Abstract: Bacterial rapid surfing motility is a novel surface adaptation of in the presence of the glycoprotein mucin. Here, we show that other Gram-negative motile bacterial species, including, ,, , and, also exhibit the physical characteristics of surfing on the surface of agar plates containing 0.4% mucin, where surfing motility was generally more rapid and less dependent on medium viscosity than was swimming motility. As previously observed in , all surfing species exhibited some level of broad-spectrum adaptive res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 38 publications
1
42
0
Order By: Relevance
“…Transcriptomic analysis also revealed a dysregulation of cell communication, which prompted us to look further into quorum-sensing (QS) signalling pathways. Our previous studies revealed the dependence of surfing motility on all three major QS pathways in P. aeruginosa [11,22]. This was also confirmed by our mutant screen since we identified suppressed surfing motility in mutants in lasI, rhlR, rhlI, pqsA-E, pqsR, pqsH, phzA1, and hcnC.…”
Section: Plos Pathogenssupporting
confidence: 88%
See 4 more Smart Citations
“…Transcriptomic analysis also revealed a dysregulation of cell communication, which prompted us to look further into quorum-sensing (QS) signalling pathways. Our previous studies revealed the dependence of surfing motility on all three major QS pathways in P. aeruginosa [11,22]. This was also confirmed by our mutant screen since we identified suppressed surfing motility in mutants in lasI, rhlR, rhlI, pqsA-E, pqsR, pqsH, phzA1, and hcnC.…”
Section: Plos Pathogenssupporting
confidence: 88%
“…Interestingly, we observed upregulation in the stringent response double mutant of the two quorum sensing regulators rhlR and pqsR, which when mutated lead to surfing deficiency [22,23] (S1 Table) and also mediate stress responses [12,27]. Since both are involved in the regulation of Pseudomonas quinolone signal (PQS) synthesis during stress [27], downstream PQS genes were further investigated and it was shown that the pqsABCDE operon, pqsH and phnAB were all downregulated (by -1.6 to -3.5-fold) in the mutant (S5 Fig).…”
Section: Identification Of Genes Required For Surfing Motility and Stmentioning
confidence: 88%
See 3 more Smart Citations